PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PENINGKATAN PEMBELAJARAN IPA TENTANG GERAK BENDA SISWA KELAS III SD - Rohanah, Siti (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Use Of Contextual Teaching And Learning Model In Improving Learning Science About The Movement Of Things For Students Of Grade III Of State Elementary School 1 Of Karangkembang. The purposes of this research was to describe proces learning of Contextual Teaching and Learning(CTL),To describe improving learning science about the movement of things for students grade III state elementary school, and to describe problems and solution the use of CTL model in improving learning science about the movement of things for student grade III state elementary school. The research was conducted in three cycles.The source data came from teachers, students, and documents. Data collection techniques is the observation, questionnaires and tests. The validity of the data using the technique of data triangulation. Learning result points out that Purpose CTL Models, can improving process and science studying result at brazes III. Keywords: CTL Models, science learning, study result. Abstrak: Penggunaan Model Contextual Teaching and Learning (CTL) dalam Peningkatan Pembelajaran IPA Tentang Gerak Benda Siswa Kelas III SD. Penelitian ini bertujuan: untuk mendeskripsikan langkah-langkah penggunaan model Contextual Teaching and Learning (CTL), dan untuk mengetahui penggunaan model Contextual Teaching and Learning (CTL) dalam pembelajaran IPA dapat meningkatkan hasil belajar IPA tentang gerak benda siswa kelas III SD. Penelitian dilaksanakan dalam tiga siklus. Sumber data berasal dari guru, siswa, dan dokumen. Teknik pengumpulan data menggunakan observasi, wawancara, tes, dan dokumentasi. Validitas data menggunakan teknik triangulasi metode dan sumber. Hasil pembelajaran menunjukkan bahwa Penggunaan Model Contextual Teaching and Learning (CTL), dapat meningkatkan proses dan hasil belajar IPA di kelas III. Kata Kunci: Model CTL,Pembelajaran IPA, hasil belajar